مدل ساختاری دردهای شکمی روان تنی کودکان ۱۰ تا ۱۲ سال بر اساس رابطه والد کودک و یادگیری اجتماعی با میانجیگری مهارتهای سازگاری. - سمیه معینی نسب; مجتبی انصاری شهی; حمیدرضا نیکیار; حسین صانعیان; امیر محسن راه نج&#1575 (Pars Journal of Medical Sciences, 2024)
Introduction: Chronic diseases such as functional abdominal pain in children cause psychological changes in addition to physical symptoms, which can increase the damage caused by this disease. Therefore, the necessity of research in the field of examining the psychological factors of these patients in order to increase their mental health is significant. The present study was conducted with the aim of determining the mediating role of adaptation skills in explaining the relationship between parent-child relationship and social learning in functional abdominal pain in 10-12-year-old children. Methods & Materils: The current research method was cross-sectional and structural equations type. The statistical population of the study included all children aged 10 to 12 years with functional abdominal pain disorder in Isfahan city in 1402. A number of 179 children were selected from the specialized clinics of digestive disorders in Isfahan based on the inclusion criteria. Data collection tools include parent-child relationship questionnaires (Pianta, 2011), learning parental pain behaviors short form, Stone, Children's Coping Behavior Questionnaire (CCBQ) and the revised abdominal pain index. To test the hypotheses, the statistical method of structural equations was used in SMART PLS-4 software. Results: The findings of the present study showed that adaptation skills can indirectly and significantly mediate the relationship between parent-child and social learning with children's functional abdominal pain (P<0.05). The direct regression paths of parent-child relationship and destructive coping with abdominal pain are equal to -0.17 and -0.24, respectively, and the direct paths of parent-child relationship and social learning to cope with the problem are equal to 0.34 and 23, respectively. It is 0.05 which is significant at the 0.05 level. Out of the six indirect paths with the mediation of the role of three behavioral adjustment styles, only two indirect paths parent-child relationship coping with the proble ، abdominal pains with regression coefficient equal to - 0.080 and t=2.23 and social learning ، destructive coping ، Abdominal pains with a regression coefficient equal to 0.050 and t=1.99 are at the p<0.05 level, which is statistically significant. This means that the strategy of coping with the problem has an indirect and meaningful effect on the child's parent's relationship and social learning with children's abdominal pain and can play a mediating role. Conclusion: Having a positive and healthy relationship between parent and child acts as a protective factor against functional abdominal pain.Creating an open space to express their feelings and needs and providing appropriate support by parents can help improve children's emotional, psychological and social problems.